The effect of home advantage, momentum, and fighting on winning in the National hockey league - Leard, B.; Doyle, J. M. (Journal of Sports Economics, 2011)
Using game-level data, the authors estimate models of team success and test for the effect of three specific factors on game outcomes in professional ice hockey. First, they estimate the home ice advantage and find that much of it can be attributed to rules advantages for the home team. Second, contrary to previous studies on momentum, the authors find some evidence that game-to-game momentum has a positive effect on winning. Finally, the authors test the impact of fighting on the likelihood of winning and find that winning fights does not lead to winning games.